2021
DOI: 10.3390/pharmaceutics13081200
|View full text |Cite
|
Sign up to set email alerts
|

Focus on the Lymphatic Route to Optimize Drug Delivery in Cardiovascular Medicine

Abstract: While oral agents have been the gold standard for cardiovascular disease therapy, the new generation of treatments is switching to other administration options that offer reduced dosing frequency and more efficacy. The lymphatic network is a unidirectional and low-pressure vascular system that is responsible for the absorption of interstitial fluids, molecules, and cells from the peripheral tissue, including the skin and the intestines. Targeting the lymphatic route for drug delivery employing traditional or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 272 publications
(314 reference statements)
0
1
0
Order By: Relevance
“…Preferential uptake into the lymphatics is highly dependent on the physicochemical properties of the particles, including size, molecular weight, surface charge, and lipophilicity [46]. Initial lymphatics draining the peritoneal submesothelial layer have favorable absorption of lipophilic and unionized compounds [47]. The study by using nonfasted rats has demonstrated that the lipoproteins in lymph are organ specific in composition, and the intestine and liver appear to be the main source of HDL that is modified during transport from the mesenteric and hepatic lymphatics to the thoracic duct [44].…”
Section: Atherosclerosismentioning
confidence: 99%
“…Preferential uptake into the lymphatics is highly dependent on the physicochemical properties of the particles, including size, molecular weight, surface charge, and lipophilicity [46]. Initial lymphatics draining the peritoneal submesothelial layer have favorable absorption of lipophilic and unionized compounds [47]. The study by using nonfasted rats has demonstrated that the lipoproteins in lymph are organ specific in composition, and the intestine and liver appear to be the main source of HDL that is modified during transport from the mesenteric and hepatic lymphatics to the thoracic duct [44].…”
Section: Atherosclerosismentioning
confidence: 99%